(untitled) (Journal of actual problems of jurisprudence, 2021)
The article studies the problems of unification of national legislative systems of member states of the Eurasian Economic Union (EAEC). At present, basic provisions of the pension legislations of the Republic of Kazakhstan, the Russian Federation, the Republic of Belarus, the Republic of Armenia and the Kyrgyz Republic differ greatly. Since the 1st of January 1998, Kazakhstan was the first among the member states to implement the defined contribution pension system, which was unrivalled among the states of the post-Soviet period. Russia, introduced a similar system in 2000, and actually abandoned the Kazakhstani model. The Republic of Armenia applies a mixed version of pensions, having implemented a funded model since January 1, 2014. The pension legislation of other participants is based on the canons of the last reform of the Soviet state. This legal imbalance radically changed qualitative and quantitative priorities in the field of pension mobility, migration flows, determining the priority of the states participating in this interstate union. The most attractive is the Russian legislation. The article analyzes some problems of the international imbalance in the system of pension migration in the EAEU countries and suggests ways of their legal solution. Key words: pension mobility, international agreements, pensions, the Eurasian Economic Union (EAEU), migration, migrant workers, labor experience, international standards, retirement age, story pension system.